Layered Epistemic System in Sufi Exegesis: Reconstructing Symbolic Interpretation for Contemporary Qur'anic Studies - Siti Rohmah; Selvy Yuspitasari (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Sufi exegesis (tafsir isyari) offers profound esoteric insights into the Qur'an, yet it frequently encounters academic skepticism due to perceived subjective biases and the absence of a systematized methodological framework. This study aims to reconstruct the methodology of symbolic interpretation in Sufi exegesis, bridging spiritual intuition with modern academic objectivity. Employing a qualitative library research design grounded in spiritual hermeneutics and historical-philosophical analysis, this research critically examines classical authoritative texts, including the works of Al-Tustari, Al-Qushayri, Al-Ghazali, and Ibn Arabi. The findings reveal that Sufi interpretation does not operate arbitrarily but functions through a novel "Layered Epistemic System" comprising textual (zahir), symbolic (isyarat), and spiritual (batin) dimensions. Within this framework, the literal meaning (zahir) serves as a rigorous epistemic control mechanism, fostering "disciplined subjectivity." Consequently, the transition from literal to spiritual meaning is mediated by intuition (dzauq and kasyf) while remaining strictly anchored in normative theological boundaries. Ultimately, this study proposes the theoretical construct of "Bounded Dynamic Epistemology," demonstrating that Sufi exegesis remains highly relevant for addressing the existential crises of contemporary modernity. It provides a robust hermeneutical paradigm that enables transformative, meaning-making encounters with the Qur'an without compromising its foundational textual integrity.